2022
DOI: 10.1123/japa.2020-0456
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Social Isolation on Physical Activity and Factors Associated With Sedentary Behavior in Older Adults During the COVID-19 Pandemic

Abstract: The objective was to analyze the impact of social isolation on moderate physical activity and factors associated with sedentary behavior of older adults during the COVID-19 pandemic. This was a cross-sectional study involving 111 older adults (aged 71.0 ± 6.87 years). The data were collected at two time points: in November 2019 and in June 2020. There was a decline in moderate physical activity when the minutes/week were compared before and during social isolation (p < .001). Sedentary behavior was associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
0
1
Order By: Relevance
“…Social isolation has been identified as a risk factor for coronary heart disease and stroke [16]. Furthermore, several studies have linked social isolation during the pandemic to reduced levels of physical activity among older adults [17][18][19][20], but additional research is needed to determine whether this translates to a worsening of glycemic control or the severity of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Social isolation has been identified as a risk factor for coronary heart disease and stroke [16]. Furthermore, several studies have linked social isolation during the pandemic to reduced levels of physical activity among older adults [17][18][19][20], but additional research is needed to determine whether this translates to a worsening of glycemic control or the severity of cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Studies have shown that loneliness and social isolation are associated with activation of the hypothalamic–pituitary–adrenal axis, leading to enhanced sympathetic nervous system activity, increased release of inflammatory cytokines, and increased oxidative stress, 10 , 11 which directly contribute to the development of T2DM. In addition, social isolation and loneliness are associated with poor weight control, 12 high tobacco uses, 13 , 14 low physical activity, 15 and poor sleep quality, 16 , 17 which indirectly increase the risk of T2DM. 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…Older adults often faced more severe public health restrictions than other populations, due to their higher vulnerability for negative outcomes ( 19 , 20 ). While these measures were crucial in preventing COVID-19 infections and lowering mortality rates, they also had adverse physical and psychosocial impacts on older adults, such as decreased social interaction and restricted access to facilities and programs, including those related to physical activity ( 21 , 22 ). As a result, opportunities for physical activity among older adults were severely limited during the pandemic, with observed declines in both incidental and structured physical activity levels ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%